Prescripción de medicamentos a pacientes ambulatorios atendidos en un Hospital de Loreto, 2023 - Sanchez Mestanza, Andrea de Fátima (2024)
This research allowed us to understand the reality regarding the prescription of medications to patients at the Regional Hospital of Loreto. Objective: To evaluate the prescription of medications to patients attended by the external consultation pharmacy service of the Regional Hospital of Loreto during the period from December 2023 to February 2024. Methodology: It was descriptive, observational, cross-sectional, prospective, and non-experimental in design. The sampling was by clusters, with the sample being the medical prescriptions attended by the external consultation pharmacy service. A total of 2792 prescriptions were analyzed from December 20, 2023, to February 10, 2024. Instruments validated by an expert judgment were used for data collection, and EXCEL 2019 and SPSS v.25 programs were used for data tabulation and analysis. Results: 100% of the prescriptions presented prescription errors; the most frequent number of prescription errors was 6, and the average was (7±1) prescription errors. Conclusions: Prescriptions handled by the outpatient clinic pharmacy service contain prescription errors